2018
DOI: 10.11591/ijpeds.v9.i4.pp1918-1925
|View full text |Cite
|
Sign up to set email alerts
|

Outdoor Performance Evaluation of Building Integrated Photovoltaic Thermal (BIPVT) Solar Collector with Spiral Flow Absorber Configurations

Abstract: Building Integrated Photovoltaic thermal solar collector (BIPVT) with Spiral flow absorber design is a collector not only used to generate electricity and thermal energy simultaneously but also can be integrated with the roof. Due to it characteristic as a roof, the collector is exposed to the direct sunlight resulting from a higher temperature on it surfaces. The temperature increased will simultaneously decrease it efficiency. An experiment has been conducted outdoor at Universiti Kebangsaan Malaysia to exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…They investigated whether the pressure drop causes a negative effect in rectangular profile finned heat sinks with natural convection [4,5,6,7]. In their study, Mousavi et al applied natural convection to the surface of a vertical finned cooling system and discussed numerical values.…”
Section: Literature Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…They investigated whether the pressure drop causes a negative effect in rectangular profile finned heat sinks with natural convection [4,5,6,7]. In their study, Mousavi et al applied natural convection to the surface of a vertical finned cooling system and discussed numerical values.…”
Section: Literature Studiesmentioning
confidence: 99%
“…where h means heat transfer coefficient over L of the fin is the equation when Pr ≥ 0.5 air hL k = 0.664 Pr 1/3 ReL 1/2 (8) provided with. If equations ( 6) and ( 8) are arranged, the heat load passing through a single finned surface according to equation (7) becomes like equation ( 9)…”
Section: Large Fin Spacingmentioning
confidence: 99%
“…The authors found that in controlling the different independent parameters, the highest electrical efficiency was the Spiral-flow design, followed by the web-flow design, and last is the oscillatory-flow design. Due to its performance and ease of construction, many authors have used the spiral-flow design in novel PV/T collectors with other features ( Ibrahim, et al, 2018;Das et al, 2021). Moreover, in recent literature (Lateef, et al, 2020 ;Abdullah, et al, 2019;Nahar, et al, 2017), the combination of different design patterns (hybrid or customized) to produce suitable novel flow configurations for either thermal or electrical performance, total improvement, or to suit specific environmental conditions has been studied.…”
Section: Introductionmentioning
confidence: 99%
“…The PVT system had improved the electrical deficiency of the PV system as heat from the panel had been extracted. The studies on PVT system had been anticipated by lots of researchers which intended to study on how it can contribute its performances in generating both electrical and heat energy [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%